Does Brand Image Moderate the Influence of Service Quality, Trust, and Price on Customer Loyality on Traveloka? - Indah Rahayu Dwiningsih; Isbandriyati Mutmainah; Dewi Fitrianti (Apollo: Journal of Tourism and Business, 2025)
This study aims to analyze the influence of service quality, customer trust, and perceived price on customer loyalty of user Traveloka, with brand image serving as a moderating variable. The research adopts a quantitative approach through a survey method involving 119 respondents who are active users of the Traveloka application in the Jabodetabek area. Respondents were selected using convenience sampling, and data were analyzed using multiple linear regression and moderated regression analysis (MRA) with the help of SPSS software. The findings reveal that service quality, customer trust, and perceived price each have a positive and statistically significant effect on loyalty. Among these factors, perceived price demonstrates the strongest influence. Additionally, brand image significantly moderates the relationship between the independent variables and loyalty, indicating that a stronger brand image enhances the positive effects of service quality, trust, and perceived price on customer loyalty. These results highlight the strategic importance of brand image in the online travel industry and suggest that improving customer experience, building trust, and offering fair pricing are essential in retaining users. This study contributes to the existing literature on consumer behavior in digital services and offers practical insights for marketing managers, particularly in the context of digital travel platforms. Strengthening brand image can be a key competitive advantage in increasing customer retention and long-term engagement.